The quality of life of children during chemotherapy treatment: an integrative review (Research, Society and Development, 2021)
Cancer and therapeutic processes can negatively interfere with the perception of health-related quality of life (HRQOL) in children. This research aims to analyze scientific productions that deal with interventions used to improve the quality of life of children with cancer during chemotherapy. The study method used was the integrative literature review, which performed six stages of the elaboration process, where the searches were in the databases: MEDLINE, CINAHL and Scopus, using the descriptors quality of life, cancer, children, chemotherapy in Portuguese and English. In the search, 479 articles were found, where 21 scientific publications were selected, which were in accordance with the established theme. The interventions found in scientific productions to improve the quality of life of children with cancer during chemotherapy treatment are: use of medication, physical exercise and yoga. There was a need to publish new articles, as well as updated Brazilian productions on the subject, aiming to improve the quality of life of children undergoing chemotherapy.